Correlation of Volleyball Extracurricular Activities Against Student Discipline at SMA Negeri 1 Panggarangan - Mukhtar Ridwan; Ayi Rahmat; Ira Arini (Universitas Majalengka, 2023)
The background of this research is the massive interest of students in volleyball extracurricular activities at school, so it can be used as a research problem in looking at the relationship between volleyball extracurricular activities and student discipline. The purpose of this study was to see the relationship between volleyball extracurricular activities and student discipline. The method in this study used a quantitative correlation method with a population of 30 people. The sampling technique in this study used total sampling with a total of 30 people. Data collection methods include questionnaires and interviews graded on a scale of 1 to 5. The data analysis technique used is the correlation and regression test. The results of proving the hypothesis by comparing the value of t count with t table are that t count > t table = 2.977 > 2.763, so that the hypothesis testing shows significant results. The magnitude of the correlation coefficient between the independent variables and the dependent variable (r) shows a value of 0.49, so that the magnitude of the coefficient of determination (KD) is 24.01%. Thus, the null hypothesis is rejected (H0) and the research hypothesis is accepted (Ha).